2020
DOI: 10.1158/0008-5472.can-19-1044
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic In Vivo Hematopoietic Stem Cell Gene Therapy with an Immune Checkpoint Inhibitor Reverses Tumor Growth in Syngeneic Mouse Tumor Models

Abstract: Population-wide testing for cancer-associated mutations has established that more than one-fifth of ovarian and breast carcinomas are associated with inherited risk. Salpingooophorectomy and/or mastectomy are currently the only effective options offered to women with high-risk germline mutations. Our goal here is to develop a long-lasting approach that provides immunoprophylaxis for mutation carriers. Our approach leverages the fact that at early stages, tumors recruit hematopoietic stem/progenitor cells (HSPC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…These are critical obstacles to a widespread application for ex vivo HSPC gene therapy of hemoglobinopathies, particularly in older patients and patients with comorbidities. We have demonstrated the safety and efficacy of this approach in several murine disease models ( 8 10 ) and, recently, in nonhuman primates ( 11 ). In both species, we have addressed a major problem associated with intravenous HDAd5/35++ injection, namely acute innate immune responses, by a prophylaxis regimen that blocked proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are critical obstacles to a widespread application for ex vivo HSPC gene therapy of hemoglobinopathies, particularly in older patients and patients with comorbidities. We have demonstrated the safety and efficacy of this approach in several murine disease models ( 8 10 ) and, recently, in nonhuman primates ( 11 ). In both species, we have addressed a major problem associated with intravenous HDAd5/35++ injection, namely acute innate immune responses, by a prophylaxis regimen that blocked proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted integration can be achieved via homology-dependent DNA repair (7). We have recently shown that our approach results in an amelioration of murine thalassemia intermedia (8), the correction of murine hemophilia (9), and the reversion of spontaneous cancer (10). First data in nonhuman primates…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mouse models have been used to study OC risk factors, including obesity [15], inflammation [16], age [8], and genetic inheritance [17], among others. Continuing the recent work on peritoneal tumor spread and systemic inflammation in an aged syngeneic female C57BL/6 mouse model of OC maintained in multiparous and nulliparous regimens [18], here, we studied the effect of parity history on the ovarian transcriptome in intact, uninduced animals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the combination with TIGIT blockade, an inhibitory NK receptor associated with T cell exhaustion phenotypes [177], increased NK cytotoxicity. Considering that current prevention methods are limited for high-risk women with germline mutations, Li et al developed a method to genetically modify hematopoietic stem/progenitor cells (HSPC) in vivo based on an integrating Ad5/35 + + vector expressing α-PD-L1-γ1 under the control of a miRNA regulation system that is activated only when HSPCs are recruited to and differentiated by the tumor into tumor-supporting cells [178]. They stablished a feasible in situ transduction strategy and demonstrated that intratumoral expression of α-PD-L1-γ1 early during tumor development successfully reduced primary tumor growth and prevention of recurrence.…”
Section: Overcoming Immunosuppressionmentioning
confidence: 99%